Primary Hyperparathyroidism in Pregnancy - Two Case Reports - Mehta, Anku (J Endocr Soc, 2021)
Introduction: Primary hyperparathyroidism in pregnancy is rare, with a reported incidence of 1%. The physiological changes of pregnancy can mask its diagnosis. Primary hyperparathyroidism is characterized by the overproduction of parathyroid hormone (PTH) and results in hypercalcemia and a raised or inappropriately normal PTH. Maternal and fetal/neonatal complications are estimated to occur in 67 and 80% of untreated cases respectively. Maternal complications include nephrolithiasis, pancreatitis, hyperemesis gravidarum, pre-eclampsia and hypercalcemic crises. Fetal complications include intrauterine growth restriction; preterm delivery and an increased risk of miscarriage. Case reports Case 1: An 18-year old woman presented in her first pregnancy with a known history of MEN type 1. She was diagnosed at the age of 17 following an appendectomy. She has a strong family history and subsequent genetic test confirmed the diagnosis of MEN1. Pre-pregnancy parathyroid sestamibi scan showed bilateral parathyroid adenoma. MRI pituitary was in keeping with a pituitary microadenoma. She had a corrected calcium ranged between 2.7-3.3mmol/L and an inappropriately raised PTH of 24.1pg/ml. She underwent elective parathyroidectomy at 15 week gestation. Post operatively she remained normocalcaemic. She subsequently developed gestational diabetes and was induced at 34 + 3 weeks due to multiple episodes of hypoglycaemia, reduced fetal movement and suspected placental insufficiency. She had a good fetal outcome. Case 2: A 29-year-old woman in her first pregnancy presented with recurrent episodes of renal colic and imaging confirmed significant bilateral renal calculi. A diagnosis of primary hyperparathyroidism was made with adjusted calcium of 2.94 mmol/L (2.20-2.60) and inappropriately unsuppressed parathyroid hormone of 20.1pg/ml (1.6-6.9), along with ultrasound parathyroid. She was managed with fluid rehydration initially and parathyroidectomy was performed at 12 weeks due to persistently elevated serum calcium. Her genetic screening for MEN (multiple endocrine Neoplasia) was negative. Fetal growth was closely monitored and the rest of her pregnancy was uncomplicated. She had an assisted vaginal delivery at term with good fetal outcome. Learning Points: 1. The physiological changes of pregnancy can mask its diagnosis; hence a high index of suspicion is needed to diagnose primary hyperparathyroidism in pregnancy.2. Management with rehydration forms the cornerstone in mild cases and Parathyroidectomy is the definitive treatment and recommended in second trimester. 3. Ultrasound is the only recommended imaging modality in pregnancy.4. Primary hyperparathyroidism can be genetically determined in 10% of cases. Genetic testing enables patients to be screened for the development of other syndrome-related diseases e.g. neuroendocrine tumours in MEN1.